A new genus and two new species of whiteflies from Australia (Hemiptera: Aleyrodidae) - Gillespie, Peter S. (Zootaxa, 2006)
Pseudosynaleurodicus gen. n. is described with two new species, P. mayoi sp. n. and P. nigrimarginatus sp. n. These new taxa have some exceptional morphological characters, including emarginate bulla-like terminal tarsal segments, two segmented legs, and features of the vasiform orifice. Placement of these taxa in the Aleurodicinae is tentative given some of their extraordinary morphological characters.